Vesicular Acetylcholine Transporter Alters Cholinergic Tone and Synaptic Plasticity in DYT1 Dystonia. Issue 12 (26th June 2021) - Tassone, Annalisa; Martella, Giuseppina; Meringolo, Maria; Vanni, Valentina; Sciamanna, Giuseppe; Ponterio, Giulia; Imbriani, Paola; Bonsi, Paola; Pisani, Antonio
ABSTRACT: Background: Acetylcholine‐mediated transmission plays a central role in the impairment of corticostriatal synaptic activity and plasticity in multiple DYT1 mouse models. However, the nature of such alteration remains unclear. Objective: The aim of the present work was to characterize the mechanistic basis of cholinergic dysfunction in DYT1 dystonia to identify potential targets for pharmacological intervention. Methods: We utilized electrophysiology recordings, immunohistochemistry, enzymatic activity assays, and Western blotting techniques to analyze in detail the cholinergic machinery in the dorsal striatum of the Tor1a +/− mouse model of DYT1 dystonia. Results: We found a significant increase in the vesicular acetylcholine transporter (VAChT) protein level, the protein responsible for loading acetylcholine (ACh) from the cytosol into synaptic vesicles, which indicates an altered cholinergic tone. Accordingly, in Tor1a +/− mice we measured a robust elevation in basal ACh content coupled to a compensatory enhancement of acetylcholinesterase (AChE) enzymatic activity. Moreover, pharmacological activation of dopamine D2 receptors, which is expected to reduce ACh levels, caused an abnormal elevation in its content, as compared to controls. Patch‐clamp recordings revealed a reduced effect of AChE inhibitors on cholinergic interneuron excitability, whereas muscarinic autoreceptor function was preserved. Finally, we tested the hypothesis that blockade of VAChT could restore corticostriatal long‐term synaptic plasticity deficits. Vesamicol, a selective VAChT inhibitor, rescued a normal expression of synaptic plasticity. Conclusions: Overall, our findings indicate that VAChT is a key player in the alterations of striatal plasticity and a novel target to normalize cholinergic dysfunction observed in DYT1 dystonia. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society Abstract : December Infographic 1 : Vesicular acetylcholine transporter alters cholinergic tone and synaptic plasticity in DYT1 dystonia